Hidden Genocides : Power, Knowledge, Memory - Irvin-Erickson, Douglas, 1982-; LaPointe, Thomas, 1962-; Hinton, Alexander Laban (Book collections on Project MUSE., 2014)
Why are some cases of genocide prominently remembered while others are ignored, hidden, or denied? In this collection, contributors approach the question from a variety of perspectives and case studies, including the suppression of discussion about indigenous populations in the Americas and Australia, the reasons why the genocide of the Armenians, Assyrians, and Greeks long remained out of sight, and the violence that was the precursor to and the aftermath of the Holocaust.